Učinki ortoze za kolk, koleno, gleženj in stopalo z vzmetjo na vzorec hoje pri otroku z diparetično obliko cerebralne paralize - Groleger Sršen, Katja (Rehabilitacija (Ljubljana), 2011)
Introduction: Cerebral palsy (CP) is a well-recognized neurodevelopmental non-progressive condition. Two thirds of children with CP are somehow able to walk, but their gait patterns are very diverse. There are very scarce data on possible effects of hip, knee, ankle and foot orthosis (HKAFO) with spring on walking pattern in child with spastic diparesis. The aim of the study was to find out whether it is possible to influence the gait pattern with internal rotation of lower limbs and hyperextension of knee by a specially designed orthosis. Methods: We present a case of a boy, using the orthosis for 18 months. Body height, weight and passive range of movement measurement and clinical and computer gait analysis were performed several times to record changes and follow up the gait pattern. Results: Clinical and computer gait analysis showed that gait pattern after 18 months of regular use of HKAFO with spring is more symmetrical and efficient, with less pronounced internal rotation of lower limbs. Conclusion: The presented case indicates that the application of HKAFO was successful. However, a longer period of follow up would be needed to see for how long the positive effects would last, even once the boy stopped using the orthosis.
Keywords: cerebralna paraliza; child; gleženj; hoja; koleno; kolk; ortotski pripomočki; ortoze; otroci; stopalo